(untitled) (Journal of Rashid Latif Medical College, 2024)
Objective: It is critical to develop planning and action plans to deal with future aging in light of the growing trend of aging, the health system's limited resources, the absence of long-term prior government planning, and the slow expansion of the productive force in society. In this sense, the goal of the study was to determine health system specialists' ideas for addressing the aging population. Methodology 29 Pakistani men and women from Lahore, Karachi, Islamabad, and Faisalabad who were experts in the fields of health and aging willingly took part in the semi-structured interview for the qualitative content analysis research. Data were classified through the use of qualitative content analysis. Results: The opinions of the experts who participated in the discussion revealed two concepts regarding the approaches taken by the Pakistani health system to deal with future aging: "executive policy" strategies, which include "evaluation and standardization," "design, planning and implementation," "strengthening demand-driven," and "modeling national and international experiences." "Preventive policies" strategies, on the other hand, include "Focus on prevention," "Focus on values and competencies," "Educational empowerment," "Knowledge-based empowerment," "Empowerment of age-related groups," "Economic empowerment," and "Social support." Conclusion: The extensive variety of approaches discussed suggests that health care must be completely prepared and tailored to the unique needs and circumstances of the aged. Using workable solutions will enable deliberate planning and prompt program and policy implementation to better handle the health system as the population ages in the future. Keywords: Aging, health system, Pakistan, qualitative, strategy